Generation of Transfer-DNA-Free Base-Edited Citrus Plants - Alquézar, Berta; Bennici, Stefania; Carmona, Lourdes; Gentile, Alessandra; Peña, Leandro (Frontiers in Plant Science, 2022)
To recover transgenic citrus plants in the most efficient manner, the use of selection marker genes is essential. In this work, it was shown that mutated forms of the ALS gene in combination with the herbicide selection agent imazapyr added to the selection medium may be used to achieve this goal. This approach enables the development of cisgenic regenerants, namely, plants without the incorporation of those bacterial genes currently employed for transgenic selection, and additionally it allows the generation of edited, non-transgenic plants with altered endogenous ALS genes leading to imazapyr resistance. In this work, citrus mutants in which ALS has been converted into imazapyr-resistant forms using a base editor system were recovered after cocultivation of the explants with Agrobacterium tumefaciens carrying a cytidine deaminase fused to nSpCas9 in the T-DNA and selecting regenerants in culture medium supplemented with imazapyr. Analysis of transgene-free plants indicated that transient expression of the T-DNA genes was sufficient to induce ALS mutations and thus generate imazapyr-resistant shoots at 11.7% frequency. To our knowledge, this is the first report of T-DNA-free edited citrus plants. Although further optimization is required to increase edition efficiency, this methodology will allow generating new citrus varieties with improved organoleptic/agronomic features without the need to use foreign genes.